KRITIK M. ARSYAD AL-BANJARI TERHADAP BEBERAPA KEPERCAYAAN MASYARAKAT BANJAR - ., Syarifuddin (UIN Antasari Banjarmasin, 2013)
The focus of this research are: (1) the forms of Banjarese beliefs in terms of: a) menyanggar banua ritual, b) membuang pesilih ritual, and c) feeding ceremonies (sasajen) to the supernatural, and (2) criticism of Shaykh Muhammad Arsyad Al Banjari against the Banjarese beliefs. According to Al-Banjari their acts were wasting valuable property (mubazzir) and following the footsteps of Satan including polytheism and worst heresy